Effects of dietary chromium propionate on growth performance, metabolism, and immune biomarkers in heat-stressed finishing pigs1. (26th December 2018) - Mayorga, Edith J; Kvidera, Sara K; Seibert, Jacob T; Horst, Erin A; Abuajamieh, Mohannad; Al-Qaisi, Mohmmad; Lei, Samantha; Ross, Jason W; Johnson, Colin D; Kremer, Brian; Ochoa, Luis; Rhoads, Robert P; et al.
Abstract: Study objectives were to determine the effects of chromium (Cr ) propionate (Cr propionate 0.04%; 0.5 g/kg of feed to deliver 200 parts per billion Cr/d; KemTRACE Cr, Kemin Industries, Inc., Des Moines, IA) on growth performance, metabolism, and health biomarkers in heat-stressed and nutrient-restricted pigs. Crossbred barrows ( n = 96; 105 ± 1 kg BW) were enlisted in an experiment conducted in two replicates, blocked by initial BW, and randomly assigned to one of six dietary-environmental treatments: (i) thermoneutral (TN ) and fed ad libitum a control diet (TNCtl ), (ii) TN and fed ad libitum a Cr supplemented diet (TNCr ), (iii) TN and pair-fed a control diet (PFCtl ), (iv) TN and pair-fed a Cr supplemented diet (PFCr ), (v) heat stress (HS ) and ad libitum fed a control diet (HSCtl ), or (vi) HS and ad libitum fed a Cr supplemented diet (HSCr ). The study consisted of three experimental periods (P). During P0 (5 d), all pigs were housed in TN conditions (21.3 ± 0.1 °C, 56.8 ± 0.3% relative humidity [RH ]) and fed the control diet ad libitum. During P1 (5 d), pigs were fed their respective dietary treatments ad libitum and kept in TN conditions. During P2 (35 d), HSCtl and HSCr-treated pigs were fed ad libitum and exposed to progressive cyclical HS conditions (27 to 31 °C, 50 ± 0.3% RH), while TNCtl, TNCr, PFCtl, and PFCr pigs remained in TN conditions and were fed ad libitum or pair-fed to their respective HSCtl and HSCr counterparts to eliminate the confounding effects of dissimilar feed intake. Overall, HS pigs had increased ( P < 0.01) rectal temperature, skin temperature, and respiration rate (0.3 °C, 3.8 °C, and 32 breaths per minute, respectively) relative to TN pigs. Overall, HS decreased ADFI and ADG (20 and 21%, respectively; P < 0.01) compared with TN controls. Final BW tended to be increased in HSCr (2.7 kg, P = 0.06) compared with HSCtl pigs. Similarly, ADG tended to be increased during P2 in HSCr relative to HSCtl-treatment (0.77 vs. 0.72 kg/d; P = 0.10). There were no effects of Cr on most production parameters, but ADFI tended to be increased in Cr relative to Ctl-fed pigs (3.19 vs. 3.09 kg/d; P = 0.08). No effects of Cr supplementation were detected on circulating glucose, insulin, NEFA, cholesterol, triglycerides, or lipopolysaccharide binding protein. However, blood neutrophils were increased in HSCr (37%; P < 0.01) relative to HSCtl pigs. In summary, these results suggest Cr supplementation may benefit growth performance during HS.